IMPLEMENTATION OF THE INDEPENDENT CURRICULUM AT THE PRIMARY SCHOOL LEVEL DRIVE SCHOOL - Raid, Naufal; Angelia, Inge (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2024)
The transition from the K13 curriculum to the independent curriculum is an effort made by the government to improve the curriculum based on developments in science and technology. The initial implementation of the independent curriculum was carried out by the driving school. In the Payakumbuh City education office there are 10 elementary school level driving schools in 2023 that have passed the selection. Before becoming driving schools, these 10 schools had implemented an independent curriculum independently. By becoming a driving school in Payakumbuh City, the independent curriculum has been revised and refined starting from KOSP, teaching modules, the Pancasila Student Profile Strengthening Project Module (P5) and matters related to the independent curriculum.